Entangled photon generation in a nonlinear microring resonator for birefringence-based sensing applications - P. P. Yupapin (2018)
This paper proposes a new concept of birefringence-based sensor using the entangled photon timing walk-off compensation. The superposition of nonlinear light known as four-wave mixing is introduced by the Kerr nonlinear effects type within the ring device. The possible two entangled photon pairs are randomly generated using the polarization control unit. Results obtained have shown that the entangled state walk-off of light traveling within the ring device can be compensated. This means the changes in walk-off parameters can be relatively measured to the changes in the applied physical parameters. The potential of using such a proposed system for birefringence-based sensor applications is plausible and discussed. © 2008 Elsevier GmbH. All rights reserved.